Endogenous Asset Ownership Structures in Deregulated Markets - Pehr-Johan Norbäck; Lars Persson (The Research Institute of Industrial Economics (IUI), 2003)
This paper determines the equilibrium ownership structure in an emerging market deregulated by privatization and investment liberalization. It is shown that bidding competition in the privatization stage is necessary but not sufficient for reaching an efficient equilibrium market structure. Competition in the ensuing entry stage is also necessary. Otherwise, one firm can induce another to take the role of the weak firm in the subsequent product market competition, by making concessions in the bidding in the privatization auction. It is also shown that Employment Guarantees may help the buyer of the privatized firm abstain from investing and by that creating a less competitive market structure.
Keywords: D44; F23; L10; L40; 330; Privatization; Ownership; FDI; Auctions; Employment Guarantees; Privatisierung; Eigentümerstruktur; Direktinvestition; Auktionstheorie